Integrative bulk and single-cell transcriptomic analysis identifies a migrasome-associated lncRNA signature predictive of prognosis and immune landscape in clear cell renal cell carcinoma - Shen, Junlin; Wang, Chun; Zhang, Mingpeng; Chen, Bin; Liu, Liwei; Tian, Jing; Shang, Zhiqun (Frontiers in Immunology, 2025)
IntroductionClear cell renal cell carcinoma (ccRCC) is characterized by high recurrence and metastasis rates, leading to poor prognosis. Migrasomes, a class of organelles mediating intercellular communication, and long noncoding RNAs (lncRNAs) both play critical roles in tumor progression; however, the prognostic significance of migrasome-associated lncRNAs in ccRCC remains unclear.MethodsMigrasome-associated lncRNAs were identified using The Cancer Genome Atlas (TCGA) dataset, and a prognostic risk signature was constructed. The associations between the model and overall survival (OS), functional enrichment, tumor mutation burden (TMB), tumor microenvironment (TME) characteristics, immune evasion, and drug sensitivity were evaluated. Single-cell transcriptomic analysis was performed to determine cell type–specific expression patterns and intercellular communication networks. Functional roles of key lncRNAs were validated in vitro using qRT-PCR, CCK-8 proliferation assays, wound-healing assays, Transwell assays, colony formation assays, immunofluorescence, and Western blotting.ResultsThe risk signature stratified patients into high- and low-risk groups with significantly different survival outcomes. High-risk patients exhibited elevated TMB and enhanced immune evasion potential. Drug sensitivity analysis revealed distinct therapeutic response profiles between the groups. Single-cell transcriptomic analysis uncovered pronounced cellular heterogeneity and TME characteristics associated with the prognostic signature. High-risk cells were predominantly enriched within tumor epithelial clusters and displayed distinct intercellular communication patterns. Knockdown of FOXD2-AS1 markedly suppressed tumor cell proliferation and migration and reduced the expression of migrasome marker proteins.DiscussionThis study presents a novel migrasome-associated lncRNA risk signature with significant prognostic and therapeutic implications for ccRCC. The signature captures distinct immune, genomic, and pharmacologic features, and its core lncRNAs may promote tumor progression through migrasome-mediated signaling pathways, warranting further mechanistic investigation.